A project review under the focus of 'complexities' on the example of exploreAT!. (5th November 2021) - Dorn, Amelie; Wandl-Vogt, Eveline; Palfinger, Thomas; Therón, Roberto; Way, Andy; Abgaz, Yalemisew; Benito, Alejandro
Abstract: This article provides insights into dealing with complexities in the Digital Humanities project exploreAT!. By exploring a non-standard language collection for cultural insights, a three-fold approach is presented looking into concrete realizations and solutions of tackling challenges in terms of Open Innovation infrastructure, technology and the topic of choice, food. Methods and processes applied and developed in the project are aimed to serve as examples for future projects with similar data sets.